Asymmetric synthesis of N-aryl sulfinamides: copper(I)-catalyzed coupling of sulfinamides with aryl iodides via kinetic resolution - Liu, Yangyuan; Wang, Zesheng; Guo, Bin; Cai, Qian (Tetrahedron letters, 2016)
[Display omitted] •A novel method for the synthesis of chiral N-aryl sulfinamides is developed.•It is a Cu-catalyzed asymmetric C–N coupling via kinetic resolution.•High conversion rate and moderate enantioselectivity are observed.•A wide range of aryl iodides are found to work well under the catalytic system. An asymmetric synthesis of N-aryl sulfinamides was achieved through copper-catalyzed coupling reactions of aryl iodides with sulfinamides. Such a kinetic resolution process provided the desired coupling products in moderate to good yields and with moderate enantioselectivities.